Follicular thyroid carcinoma invades venous rather than lymphatic vessels - Liu Yulin; Zhu Bing; Lin Xiaoqi; Silverman Jan F (BMC, 2010)
Abstract Follicular thyroid carcinoma (FTC) tends to metastasize to remote organs rather than local lymph nodes. Separation of FTC from follicular thyroid adenoma (FTA) relies on detection of vascular and/or capsular invasion. We investigated which vascular markers, CD31, CD34 and D2-40 (lymphatic vessel marker), can best evaluate vascular invasion and why FTC tends to metastasize via blood stream to remote organs. Thirty two FTCs and 34 FTAs were retrieved for evaluation. The average age of patients with FTA was 8 years younger than FTC (p = 0.02). The female to male ratio for follicular neoplasm was 25:8. The average size of FTC was larger than FTA (p = 0.003). Fourteen of 32 (44%) FTCs showed venous invasion and none showed lymphatic invasion, with positive CD31 and CD34 staining and negative D2-40 staining of the involved vessels. The average number of involved vessels was 0.88 ± 1.29 with a range from 0 to 5, and the average diameter of involved vessels was 0.068 ± 0.027 mm. None of the 34 FTAs showed vascular invasion. CD31 staining demonstrated more specific staining of vascular endothelial cells than CD34, with less background staining. We recommended using CD31 rather than CD34 and/or D2-40 in confirming/excluding vascular invasion in difficult cases. All identified FTCs with vascular invasions showed involvement of venous channels, rather than lymphatic spaces, suggesting that FTCs prefer to metastasize via veins to distant organs, instead of lymphatic vessels to local lymph nodes, which correlates with previous clinical observations.